PENGETAHUAN GIZI IBU BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA : STUDI KASUS-KONTROL DI PUSKESMAS GUNTUNG MANGGIS - Siti Aisyah Solechah; Norhasanah Norhasanah; Yuliana Salman (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
This study aimed to analyze the relation of mothers’ nutrition knowledge and attitudes and dietary patterns of children under five to the incidence of stunting among children under five in the working area of Puskemas Guntung Manggis. This study used a case-control design. It was conducted from January to August 2021. A total of 58 children under five and their mothers (29 children and their mothers in the case group and 29 in the control group) participated in this study. The data were collected through interviews using questionnaires. The data were analyzed using the chi-square test. Mothers’ nutrition knowledge had a significant association (p=0,002) with the incidence of stunting in children under five. Mothers with low nutrition knowledge had 8,089 times higher risks (95% CI: 1,996-32,787) of having stunted children. Mothers’ nutrition attitudes (p=0,313) and dietary patterns of children under five consisting of consumption frequency of staple foods (p=0,792), fat sources (p=0,793), protein sources (p=0,430), vegetables (p=0,293), and fruits (p=0,793) had no significant relationships with the incidence of stunting in children under five. It can be concluded that mothers’ nutrition knowledge was associated with the incidence of stunting in children under five in the working area of Puskesmas Guntung Manggis.